Implementing Health Behavior Change Consultations for Adult Patients in a Free Student-Led Interprofessional Community Clinic - Kumar, Esha; Konsor, Madeline; Sampson, Jessica; Schneider, Kristin (Journal of Student-Run Clinics, 2022)
In 2018, the behavioral health clinic within the Interprofessional Community Clinic, a student-led free clinic in Lake County, Illinois, expanded its mental health services by implementing health behavior change consultations (HBCCs) during primary care appointments. HBCCs are conducted by psychology graduate students and are designed to help patients implement behavior and lifestyle changes to improve overall health. Consults are requested by the medical team to assist patients with developing strategies for reasons such as weight management, increasing physical activity, and medication adherence. An HBCC consultant discusses current lifestyle behaviors, identifies motivations and barriers to making change, and assists the patient with goal-setting. Follow-up with patients often occurs during their subsequent medical appointments to monitor progress, reassess goals, and troubleshoot barriers. Since 2018, the utilization of HBCCs increased to an average of one out of six patients receiving an HBCC per clinic day. This descriptive report describes the implementation of HBCCs, a patient case example of an HBCC, and strategies to help student-led clinics implement similar services. Integrating behavior change appointments in student-led clinics through the use of HBCC can help reduce some of the burden on primary care providers and help patients better manage their health conditions.